Excellent efficacy and beneficial safety during observational 5-year follow-up of rapid steroid withdrawal after renal transplantation (Harmony FU study): original article - Stumpf, Julian David Christopher; Thomusch, Oliver; Opgenoorth, Mirian; Wiesener, Michael; Pascher, Andreas; Woitas, Rainer Peter; Suwelack, Barbara; Rentsch, Markus; Witzke, Oliver; Rath, Thomas; Banas, Bernhard; Benck, Urs Tobias; et al. (Nephrology, dialysis, transplantation, 2024)
We previously reported excellent efficacy and improved safety aspects of rapid steroid withdrawal (RSWD) in the randomized controlled 1-year “Harmony” trial with 587 predominantly deceased-donor kidney transplant recipients randomized either to basiliximab or rabbit antithymocyte globulin induction therapy and compared with standard immunosuppressive therapy consisting of basiliximab, low tacrolimus once daily, mycophenolate mofetil and corticosteroids.The 5-year post-trial follow-up (FU) data were obtained in an observational manner at a 3- and a 5-year visit only for those Harmony patients who consented to participate and covered clinical events that occurred from the second year onwards.Biopsy-proven acute rejection and death-censored graft loss rates remained low and independent of RSWD. Rapid steroid withdrawal was an independent positive factor for patient survival (adjusted hazard ratio 0.554, 95% confidence interval 0.314-0.976; P = .041).The reduced incidence of post-transplantation diabetes mellitus in RSWD patients during the original 1-year study period was not compensated by later incidences during FU. Incidences of other important outcome parameters such as opportunistic infections, malignancies, cardiovascular morbidity/risk factors, donor-specific antibody formation or kidney function did not differ during FU period.With all the limitations of a post-trial FU study, the Harmony FU data confirm excellent efficacy and beneficial safety aspects of RSWD under modern immunosuppressive therapy over the course of 5 years after kidney transplantation in an immunologically low-risk, elderly population of Caucasian kidney transplant recipients.Trial registration: Clinical trial registration number: Investigator Initiated Trial (NCT 00724022, FU study DRKS00005786)